176k views
0 votes
Match each differential equation to a function which is a solution.

FUNCTIONS
A. y=3x+x2y=3x+x2,
B. y=e−4xy=e−4x,
C. y=sin(x)y=sin⁡(x),
D. y=x12y=x12,
E. y=6e3xy=6e3x,

Differential Equations

1. y″+y=0y″+y=0
2. y′=3yy′=3y
3. 2x2y″+3xy′=y2x2y″+3xy′=y
4. y″+6y′+8y=0y″+6y′+8y=0

1 Answer

4 votes

Answer: 1 - C

2 - E

3 - no answer

4 - B

Explanation:

A.
y = 3x+x^2


y' = 3 + 2x\\y'' = 2

  • Replace in 1:


y'' + y = 0


2 + 3x + x^2 \\eq 0

So, A is not an answer for 1

  • Replace in 2:


y' = 3y


3+2x = 3(3x + x^2)

So, A is not an answer for 2

  • Replace in 3


2x^2y'' + 3xy'= y


2x^2(2) + 3x(3 + 2x) = 4x^2 + 9x + 6x^2 \\eq 3x+x^2

So, A is not an answer for 3

  • Replace in 4


y'' + 6y' + 8y = 0


2 + 6(3+2x)+8(3x + x^2) = 2+18+12x+24x+8x^2 \\eq 0

So, A is not an answer for 4

B.
y = e^(-4x)


y' = -4e^(-4x)


y'' = 16e^(-4x)

  • Replace in 1


y'' + y = 0


16e^(-4x) -4e^(-4x) = 12e^(-4x) \\eq 0

So, B is not an answer for 1

  • Replace in 2


y' = 3y


-4e^(-4x) \\eq 3e^(-4x)

So, B is not an answer for 2

  • Replace in 3


2x^2y'' + 3xy' = y


2x^2(16e^(-4x)) +3x(-4e^(-4x)) \\eq  e^(-4x)

So, B is not an answer for 3

  • Replace in 4


y'' + 6y' +8y = 0


16e^(-4x) + 6(-4e^(-4x)) + 8e^(-4x) = e^(-4x)(16-24+8) = 0

So, B is an answer for 4

C.
y = sin(x)


y' = cos(x)


y'' = -sin(x)

  • Replace in 1


y'' + y = 0


-sin(x) + sin(x) = 0

So, C is an answer for 1

We jump to

D.
y = x^(12)


y' = 12x^(11)


y'' = 132 x^(10)

  • Replace in 2


y' = 3y


12x^(11) \\eq 3x^(12)

So, D is not an answer for 2

  • Replace in 3


2x^2y'' + 3xy' = y


2x^2(132x^(10)) + 3x(12x^(11)) = 300x^(12) \\eq x^(12)

So, D is not an answer for 3

E.
y = 6e^(3x)


y' = 18e^(3x)


y'' = 54e^(3x)

  • Replace in 2


y' = 3y


18e^(3x) = 3(6e^(3x)) = 18e^(3x)

So, E is an answer for 2

User Khary
by
5.4k points